Implementation of AML Directive into Polish Legal System - Citi Handlowy Experience - Iwonin, Elżbieta (Advanced Information Technologies for Management – AITM 2009, 2009)
The purpose of the article is to clarify interesting aspects and the positive results of the consultation process during the legislative works on the project of amendment of the Act on Counteracting Introduction into Financial Circulation of Property Values derived from Illegal or Undisclosed Sources and on Counteracting the Financing of Terrorism of November 16, 2000 - Polish AML Act. The article is an attempt to predict the potential problems the covered institutions may have in the implementation process what was described in Section 4. The rest of the article presents new approach to the relationship with the customer imposed by the Directive and the impact which new obligations may have on covered institutions. There are proposals how the internal procedures need to be amended, how the customers should be verified and finally what minimal enhancements of the systems supporting the process are required. Citi Handlowy, being the subsidiary of the US financial institution, has already implemented many elements of new AML Act as a result of applying of FATF1 regulations by the Parent Company. Based on this experience the article focuses on practical aspects of Know Your Customer programme implementation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 106-117